PENERAPAN BRAINSTORMING DENGAN TEKNIK TERKENDALI / TERARAH UNTUK MENINGKATKAN HASIL BELAJAR MENYUSUN OPINI BENTUK ARTIKEL - Brigita Febrinda Inggriani; Martono Martono; Antonius Totok Priyadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This research is classroom action research. The subjects in this study were 36 students of class XII IPS 1 SMAN 2 Sekayam. Data collection techniques using observation, performance tests, field notes and documentation. The research procedure includes planning, action, observation and reflection. Performance indicators in this study if student learning outcomes reach a percentage of 80%, the average result of opinion writing skills in the form of articles is 77.00 and the number of students complete the KKM with a percentage of 77%. The results of the study: (1) increased skills in compiling opinions in the form of articles, in the pre-cycle of 67.94; in the first cycle of 72.71; and in the second cycle of 83.51. (2) The increase in students completing the KKM, in the pre-cycle students who completed the KKM as many as 8 students out of 36 students with a percentage of 22%, the first cycle students completed the KKM as many as 15 students from 36 students with a percentage of 42% and in the second cycle students completed the KKM as many as 33 students of 36 students with a percentage of 92%.